Energy, exergy, and emission (3E) analysis of hydrogen-enriched waste biodiesel-diesel fuel blends on an indirect injection dual-fuel CI engine - Bayramoglu, Kubilay; Bayramoglu, Tolga; Polat, Fikret; Saridemir, Suat; Alcelik, Necdet; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Limited fossil energy reserves and rising energy costs increase the importance of alternative renewable energy sources and more efficient use of energy. Hydrogen gas is an alternative renewable energy source for internal combustion engines due to its high combustion efficiency and lower calorific value and near-zero emissions. For more efficient and effective use of internal combustion engines, exergy analysis is also important along with energy analysis. In this study, biodiesel fuel obtained from waste cooking oil was blended with 20 % diesel fuel. Energy and exergy analyses were performed for the test fuels obtained by adding hydrogen at different ratios to the resulting fuel mixture. The experiments were carried out on a 3-cylinder, water-cooled, pre-combustion chamber diesel engine at a constant engine speed of 2200 rpm and under different loads (15 Nm, 30 Nm, 45 Nm and 60 Nm). Fuel energy ratio was calculated as 17.84 kW, 19.71 kW, 18.03 kW, 17.89 kW and 17.86 kW for D100, B20, B20H10, B20H20, B20H30 and B20H40 fuel blends, respectively. It was observed that heat loss increased by 10 %, mechanical energy rate increased by 100 % and exhaust energy rate increased by 57 % when 30 Nm torque energy flow rates were compared with 15 Nm torque case. Compared to 15 Nm engine load, fuel, exhaust, mechanical work and heat loss energy flow increases by 200 %, 300 %, 300 % and 100 % for 60 Nm engine load. The exergy destruction rate declines with increased engine loads. The exergy destruction rate constitutes approximately 46.7 % of the total exergy rate for 60 Nm engine load. The highest first- and second- law efficiencies for all test fuel are detected when the engine runs at 45 Nm. At this engine load, the first law efficiency is calculated to be 29.53 %, 27.91 %, 28.94 %, 29.4 %, 29.72 %, and 30.47 %, and the second law efficiency is calculated to be 27.62 %, 26.08 %, 27.05 %, 27.50 %, 27.81 %, and 28.52 % for D100, B20, B20+H10, B20+H20, B20+H30, and B20+H40.
Keywords: Alternatives fuels; Hydrogen; Energy analysis; Exergy analysis; Thermodynamic; COOKING OIL; PERFORMANCE; COMBUSTION; Thermodynamics; Energy & Fuels